PENANGANAN MISSING DATA PADA RANCANGAN BLOK RANDOM LENGKAP - ROSA SELLY YUDIASARI (MATHunesa: Jurnal Ilmiah Matematika, 2014)
Abstract Missing data on randomized complete block design ( RCBD ) is information that is not available for an object (case) specific, where the number of data observations in a randomized complete block design less than k x n observational data. Missing data resulted in difficulty in the analysis of the data, because the data obtained isn’t complete. So we need an missing data approach on RCBD, the exact analysis and approximation analysis. In this thesis discusses the handling of missing data in the RCBD with approximation analysis using Yates and Biggers method, because there is correspondence between formulas with the experimental design. Yates is a method of approximation methods for missing data handling with minimizing the sum of squared errors, while the Biggers method is a method of estimation of missing data with a matrix approach. Then to overcome the bias on the sum of squares treatment needed analysis of variants alternative table as an alternative to the analysis of missing data on RCBD and determine the effect of treatment on the response of the observation. Then for one and two missing data can be solved by using the method of Yates. For four missing data can be solved by the method of Biggers and three missing data can be solved by using Baten’s rule and a matrix approach on Biggers method. Keywords: missing data, a randomized complete block design, approximation analysis, the Yates method, Biggers method, the analysis of variants alternative. Abstrak Missing data pada rancangan blok random lengkap (RBRL) merupakan informasi yang tidak tersedia untuk sebuah obyek (kasus) tertentu, dimana banyaknya data pengamatan dalam rancangan blok random lengkap kurang dari kxn data pengamatan. Missing data mengakibatkan kesulitan pada analisis data, karena data yang diperoleh tidak lengkap. Sehingga perlu dilakukan pendekatan terhadap missing data pada RBRL, yaitu analisis eksak dan analisis pendugaan. Dalam skripsi ini membahas penanganan missing data pada RBRL dengan analisis pendugaan menggunakan metode Yates dan metode Biggers, karena terdapat kesesuaian antara formula dengan rancangan percobaan. Metode Yates merupakan metode pendugaan untuk menangani missing data yang dilakukan dengan meminimumkan jumlah kuadrat error, sedangakan metode Biggers merupakan metode pendugaan missing data dengan pendekatan matrik. Kemudian untuk mengatasi bias pada jumlah kuadrat perlakuan diperlukan tabel analisis varian alternatif sebagai alternatif analisis missing data pada RBRL dan mengetahui pengaruh perlakuan terhadap respon pengamatan. Maka untuk satu dan dua missing data dapat diselesaikan dengan menggunakan metode Yates. Untuk empat missing data dapat diselesaikan dengan metode Biggers dan tiga missing data dapat diselesaikan dengan menggunakan aturan Baten dan pendekatan matriks pada metode Biggers. Kata Kunci : missing data, rancangan blok random lengkap, analisis pendugaan, metode Yates, metode biggers, analisis varian alternatif.